Parametric finite-volume method for Saint Venant's torsion of arbitrarily shaped cross sections. (15th January 2021) - Chen, Heze; Gomez, Jose; Pindera, Marek-Jerzy
Highlights: A novel finite-volume method for torsion of arbitrarily shaped bars is constructed. Explicit expressions for local stiffness matrix elements facilitate implementation. Assessment and verification using elasticity solutions demonstrate the method's accuracy. Grading enhances torsional rigidity in bio-like constructs with extreme curvatures. Warping of elliptical cross sections through appropriate lamination is eliminated. Abstract: We extend our recent finite-volume based approach to the solution of Saint Venant's torsion problems of bars and beams comprised of rectangular sections to enable analysis of arbitrary cross sections characterized by curved boundaries. This is accomplished by incorporating parametric mapping based on transfinite grid generation to enable discretization of the bar cross section by quadrilateral rather than rectangular subvolumes employed in the original version. The construction of the local stiffness matrix that relates the surface-averaged subvolume warping functions to the corresponding tractions is carried out in the reference plane such that the subvolume equilibrium in the physical plane is satisfied in a surface-averaged sense. This produces explicit expressions for the stiffness matrix elements that may be readily coded. Orthotropic subvolumes are intrinsic in the method's construction so that bars with heterogeneous and composite microstructures may be analyzed. The convergence and accuracy of the parametric finite-volume method are assessed and verified upon comparison with exact elasticity solutions for cross sections with convex and concave boundaries. Examples involving structural applications of prismatic bars with curved boundaries illustrate the utility of the developed methodology. These include cross sections that resemble biological constructs with homogeneous and graded regions aimed at enhancing torsional rigidities, as well as homogeneous and graded elliptical cross sections with orthotropic shear moduli aimed at reducing and eliminating warping. We demonstrate for the first time that by laminating an elliptical cross section with alternating stiff and soft isotropic layers in a manner that mimics the required orthotropic moduli at the homogenized level, warping can be practically eliminated with sufficient microstructural refinement.